2018
DOI: 10.1002/nme.5762
|View full text |Cite
|
Sign up to set email alerts
|

Spatial stability for the monolithic and sequential methods with various space discretizations in poroelasticity

Abstract: Summary We investigate spatial stability with various numerical discretizations in displacement and pressure fields for poroelasticity. We study 2 sources of the early time instability: discontinuity of pressure and violation of the inf‐sup condition. We consider both compressible and incompressible fluids by employing the monolithic, stabilized monolithic, and fixed‐stress sequential methods. Four different spatial discretization schemes are used: Q1Q1, Q2Q1, Q1P0, and Q2P0. From mathematic analysis and numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 53 publications
(144 reference statements)
0
14
0
Order By: Relevance
“…The results obtained from their works show good convergence behavior and do not exhibit spurious pressure modes. Further detailed comparative studies of the stability of these elements have been reported in Yoon and Kim 120 …”
Section: Finite Element Formulationmentioning
confidence: 97%
“…The results obtained from their works show good convergence behavior and do not exhibit spurious pressure modes. Further detailed comparative studies of the stability of these elements have been reported in Yoon and Kim 120 …”
Section: Finite Element Formulationmentioning
confidence: 97%
“…This mixed spatial discretization provides a relatively stable pressure field for the early‐time behavior of poromechanics, allowing a discontinuous pressure field caused by instantaneous pressure build‐up. Whereas the mixed spatial discretization may cause checkerboard‐type pressure oscillations when the monolithic method is employed, resulting in a violation of the inf‐sup condition, the fixed‐stress sequential method, described in the following section, can prevent this violation from occurring 14 . A block‐partitioned preconditioning skill based on the fixed‐stress sequential approach can solve the linear system of the monolith method with more computational efficiency, avoiding violation of the inf‐sup condition, although the direct method of matrix solution is used for the monolithic method 44 .…”
Section: Mathematical Description Of Poroelasticitymentioning
confidence: 99%
“…Several stabilization techniques have been proposed for spatial stability for the equal‐order approximations 46–48 . In this case, the fixed‐stress method can stabilize spatial solution effectively 14 …”
Section: Mathematical Description Of Poroelasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…This has motivated a number of poromechanical formulations that have combined a locally conservative method for the fluid flow equation with CG discretization of the solid deformation equation. The types of locally conservative methods used for this purpose include the finite volume method, the Raviart‐Thomas mixed finite element method, the discontinuous Galerkin (DG) method, and the enriched Galerkin (EG) method . These studies have shown that the use of a locally conservative method enables more robust solution of the fluid flow equation in a poromechanical problem.…”
Section: Introductionmentioning
confidence: 99%